The Effect of Self-Efficacy, Learning Motivation, and Entrepreneurship Education on Entrepreneurial Intention - Natasya Putri Tama; Besse Wediawati; Feny Tialonawarmi (Universitas Darwan Ali, 2026)
The high unemployment rate among university graduates highlights the urgency of accelerating entrepreneurial interest among students during their college years. This study is designed to map the impact of self-efficacy, learning motivation, and entrepreneurship education on students' entrepreneurial interest at the Faculty of Economics and Business, Universitas Jambi. A quantitative method with descriptive and verification approaches was applied. A total of 98 students were selected as respondents using a proportional stratified random sampling technique. Data were collected through a structured questionnaire with a Likert scale and subsequently analyzed using variance-based structural equation modeling (SmartPLS). The results demonstrate that self-efficacy, learning motivation, and entrepreneurship education both individually and collectively contribute positively and significantly to shaping students' entrepreneurial interest. This study provides important implications that developing students' entrepreneurial spirit should not rely solely on academic material, but must also address the strengthening of individual mentality and internal motivation